Analytical evaluation of P2P reputation systems. (1st January 2012) - Lagesse, Brent
Despite widespread use of reputation mechanisms in P2P systems, little has been done in the area of analytical evaluation of these mechanisms. Current approaches for evaluation involve simulation and experimentation. These approaches provide evaluation of the mechanism in a few settings in which the experiment is designed; however, it is difficult to use these simulations for direct comparison of reputation mechanisms over a large number of systems and attacker models. In this paper, we present several analytical metrics and a utilitybased method for evaluating reputation mechanisms. Further, we provide a case study of an evaluation of the EigenTrust reputation mechanism to demonstrate the use of these metrics and methods.